Neural oscillations during acupuncture imagery partially parallel that of real needling - Zhang, Hao; Liu, Qingxia; Yao, Menglin; Zhang, Zhiling; Chen, Xiu; Luo, Hua; Ruan, Lili; Liu, Tianpeng; Chen, Yingshuang; Ruan, Jianghai (Frontiers in Neuroscience, 2023)
Tasks involving mental practice, relying on the cognitive rehearsal of physical motors or other activities, have been reported to have similar patterns of brain activity to overt execution. In this study, we introduced a novel imagination task called, acupuncture imagery. Healthy volunteers were guided to watch a video of real needling in the left and right KI3(Taixi point). The subjects were then asked to perform tasks to keep their thoughts in three one-minute states alternately: resting state, needling imagery left KI3, and needling imagery right KI3. Another group experienced real needling in the right KI3. A 31-channel-EEG was synchronously recorded for each subject. EEG microstate analyses were performed to depict the brain dynamics during these tasks. Compared to the resting state, both acupuncture needling imagination and real needling in KI3 could introduce significant changes in neural dynamic oscillations. Moreover, the parameters involving MsA of needling imagery in the right KI3 showed similar changes as real needling in the right KI3. These results confirm that needling imagination and real needling have similar brain activation patterns. Needling imagery may change brain network activity and play a role in neural regulation. Further studies are needed to explore the effects of acupuncture imagery and the potential application of acupuncture imagery in disease recovery.